2015
DOI: 10.4161/15592324.2014.989758
|View full text |Cite
|
Sign up to set email alerts
|

Crossroads of stress responses, development and flowering regulation—the multiple roles of Cyclic Nucleotide Gated Ion Channel 2

Abstract: The Arabidopsis autoimmune mutant, defense-no death 1 (dnd1) is a null mutant of CYCLIC NUCLEOTIDE-GATED ION CHANNEL2 (AtCNGC2). dnd1 exhibits constitutive pathogen resistance responses including higher levels of endogenous salicylic acid (SA), which is an important signaling molecule for pathogen defense responses. Recently we have reported that dnd1 exhibits a significantly delayed flowering phenotype, indicating the involvement of AtCNGC2 in flowering transition. However, since SA has been known to influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…SA also has long been proposed as a signal for flowering [11]. Consistent with this possibility, the early flowering phenotype observed in several Arabidopsis mutants correlates with, and is dependent on, elevated SA levels [1215]. In addition, flowering was delayed in one study of SA-deficient Arabidopsis [16], although others failed to observe this phenomenon [17, 18].…”
Section: How Was Sa’s Status As a Hormone Discovered?mentioning
confidence: 90%
See 1 more Smart Citation
“…SA also has long been proposed as a signal for flowering [11]. Consistent with this possibility, the early flowering phenotype observed in several Arabidopsis mutants correlates with, and is dependent on, elevated SA levels [1215]. In addition, flowering was delayed in one study of SA-deficient Arabidopsis [16], although others failed to observe this phenomenon [17, 18].…”
Section: How Was Sa’s Status As a Hormone Discovered?mentioning
confidence: 90%
“…In addition, flowering was delayed in one study of SA-deficient Arabidopsis [16], although others failed to observe this phenomenon [17, 18]. Interestingly, several proteins that regulate both flowering and resistance signaling have been identified [12, 13, 15, 1721]. While this finding suggests an interconnection between flowering and disease resistance [22], it is clearly complex: some of these proteins regulate both resistance and flowering in an SA-dependent manner, whereas several others regulate resistance via an SA-dependent pathway but positively or negatively regulate flowering via an SA-independent mechanism.…”
Section: How Was Sa’s Status As a Hormone Discovered?mentioning
confidence: 99%
“…In Arabidopsis , DND1/CNGC2 has been reported to play a role in flowering timing and fertility (Chaiwongsar et al 2009 ; Chin et al 2013 ). Fortuna et al ( 2015 ) reported that the role of DND1 in flowering timing is independent from SA accumulation, and independent from its role in pathogen defense. Further investigations are necessary to determine whether disease resistance can be achieved in tomato without reduced fertility by decreased expression level or altered functionality of SlDND1 .…”
Section: Discussionmentioning
confidence: 99%
“… 25 30 Several members of Arabidopsis CNGC Groups I–III regulate various functions such as plant development and stress tolerance, 25 , 31 seed germination, 32 plant growth, 33 pollen fertility under stress, 5 pollen tip growth 34 and pathogen defence. 35 , 36 However, AtCNGC2 and AtCNGC4 , members of Group IVb, played their role in disease resistance against various pathogens and in thermotolerance, 29 , 37 44 while AtCNGC19 and AtCNGC20 , members of Group IVa, are involved in abiotic salt stress responses. 19 , 45 47 Whether plant CNGC genes are functionally distinguished in a group-dependent manner is not clear.…”
Section: Introductionmentioning
confidence: 99%